The role of diltiazem on asetic acid induced colitis in rats - Ömer ÖZÜTEMİZ and Belkıs ÜNSAL and Murat ALKANAT and Kadir AKSÖZ and Çiğdem DİNÇER and Yücel BATUR (Turkish Journal of Gastroenterology, 2019)
-